Proof. The equivalence of (2) and (3) is easy to derive (and well known). Indeed, assuming (2), we infer that T is similar to A -1/2TA1/2 = A112BA112, which is nonnegative, where the invertibility of AlI2 follows from that of A. On the other hand, if (3) holds, say T = X- ‘CX, where X is invertible and C >, 0, then T = (X-‘X-‘*)(X*CX) is the product of the positive XP’X-‘* and the nonnegative X*CX. This proves (2). To complete the proof, we need only show that (1) * (3). Assume that (1) is true. Since the property of being the product of two nonnegative matrices is preserved under similarity, we may, in view of the Jordan canonical form for matrices, assume that T = T,@T, on the space H = H,@ H,, where Tl is
invertible and T, is nilpotent. It is easily seen that H, = ran T” and H, = ker T”. Let S = A1/2BA1/2, K, = ran S”, and K, = ker S”. Since S is non- negative, K, and K, are orthogonal complements to each other. From A112S = TA1/2, we deduce that A112S” = TnA112, whence A112K, G H, and A’i2K2 c H,. It follows that A1/2*Hl’ G KIL and A112*H21 c K21, or, equiv-